PEMELIHARAAN DAN PENGHAPUSAN ASET KENDARAAN DINAS OPERASIONAL PADA KANTOR DINAS KEHUTANAN DAN KONSERVASI PROVINSI PAPUA TAHUN 2009-2012 - MAY, ANASTASIA ([Yogyakarta] : Universitas Gadjah Mada, 2015)
The research that has been done have a purpose to know maximization of existingmaintenance and usage of vehicle service as means of transport that used to support the work, as well as elimination of asset service vehicle already not worth sharing in accordance with the applicable procedure in The Office of The Department Of Forestry And Conservation Of Papua Province. The research conducted through the interview process with the civil servants concerned and observation of vehicle service as an object of research. The research results are obtained using SWOT analysis to know the problems encountered and find the right solution as a possible solution to improve the performance of government. From the results of the SWOT analysis it is known that maintenance and service of the vehicle utilization for civil servants have not been done to the maximum because of the use of budget reporting problems to the Central Government which is still done manually, so it is not uncommon the proposed budget can not be accessed just in time. The lack of operational funds cause the vehicle cannot be used. This certainly will hamper civil servants in carrying out its work. The management and removal of vehicles department also hasn’t been arranged neatly because it has not been applied to the prevailing mechanism. Therefore, need for technology-based training administration to improve the performance of civil servants in terms of reporting and asset management.